Association of hMSH5 C85T polymorphism with radiation sensitivity of testicular cell lines GC‐1, GC‐2, TM3, and TM4. (8th May 2020) - Lin, Mingyue; Guo, Lihuang; Cheng, Zhenbo; Huan, Xisha; Huang, Yue; Xu, Keqian
Abstract: Background: The hMSH5 C85T polymorphism, which encodes hMSH5 P29S, is associated with individual differences in spermatogenic abnormalities caused by ionizing radiation (IR), but the molecular mechanisms remain unclear. Objectives: This manuscript aims to explore the role of hMSH5 C85T polymorphism in IR‐induced individual differences in spermatogenic abnormalities. Material and methods: We transfected pcDNA‐hMSH5 P29S vector into mouse spermatogonia GC‐1, mouse spermatocytes GC‐2, mouse testicular mesenchymal cells TM3, and mouse testicular support cells TM4. After radiation, we evaluated cell survival with colony formation assay, apoptosis with TUNEL assay and caspase‐3 activity assay, DNA damage with comet assay and an in vivo NHEJ activity assay. Results: Results showed that only spermatocytes GC‐2 transfected with pcDNA‐hMSH5 P29S vector had significant differences in IR‐induced cell survival and apoptosis when compared to that transfected with pcDNA empty vector and pcDNA‐wild‐hMSH5 vector, while there was no statistical difference in GC‐1, TM3, and TM4. In addition, comet assay showed that the DNA damage of GC‐2 transfected with pcDNA‐hMSH5 P29S vector increased significantly compared to that transfected with pcDNA empty vector and pcDNA‐wild‐hMSH5 vector after IR. And in vivo NHEJ activity assay showed that the NHEJ activity of GC‐2 transfected with pcDNA‐hMSH5 P29S vector was statistically higher than that transfected with pcDNA empty vector and pcDNA‐wild‐hMSH5 vector. Conclusion: Our study indicates that the hMSH5 C85T polymorphism leads to an abnormal increase in apoptosis and lessen the control on error‐prone NHEJ of spermatocyte GC‐2, thereby altering the difference of radiation sensitivity of spermatogenesis.